Relationship between E. coli and Toxicant Contamination in Primary School Canteen Food based on Region and Level in Surabaya, 2017 - Alda Dini Wijayanti; Linda Dewanti; Ema Qurnianingsih (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Primary students are still in the developing phase, so they still need enough nutrition. The food source they consume is not only originated from home but also from school snacks. However, it can be said that school snacks can be easily contaminated by E.coli and Hazardous and Toxic Substances (HTS) or toxicant. School plays a major role to regulate the canteen. Therefore, this study aims to know whether there is a relation between the monitoring and controlling of school snacks which E.coli and toxicant free food and the relation of the contaminated foods with the school zone and school status. Methods: This research was conducted with analytics study from secondary datum from the result of the snacks investigation by the Public Health Office of Surabaya on primary school in 2017. Results: The results of this study stated that there is no relationship between E.coli contamination in snacks and cooking utensils and toxicant contamination in snacks with the school region and status in Surabaya. Conclusion: It is needed to enhance the supervision of the school especially for primary school to increase healthy food in school canteen whether it is public school or private school.